Marketing Innovation of Melayu Songket Deli Through Podcasts - Sinar, Tengku Silvana; Ganie, Rohani; Lubis, Tasnim; Syarfina, Tengku (Universitas Negeri Medan, 2025)
This research aims to improve digital marketing capabilities for the IR & IR - Melayu Craft Joint Business Group (KUB) in Bandar Khalipah Village, Deli Serdang Regency, through training in the use of podcast media. This community service program is designed to overcome these obstacles by utilizing podcast technology as a marketing tool. The research method involves several stages: submission of proposals, preparation of training materials,implementation, and monitoring and evaluation. The training lasted for six months, with lecture sessions, questionsand answers, and practice regarding podcast creation and promotion. Participants are trained to create interestingpodcast content, manage and promote it effectively. The research results show significant improvements in severalaspects. Sales of songket products increased by 30% after implementing podcasts in marketing strategies, indicatingthe effectiveness of this method in expanding market reach and increasing consumer awareness. Additionally, therewas a 40% increase in KUB members' digital marketing skills, reflected in better podcast quality. Members' ability to use data analysis tools also increases, enabling them to understand market dynamics in real-time and make more strategic marketing decisions